INVESTASI DAN GAYA HIDUP INVESTOR PEREMPUAN MODERN DI KOTA PALEMBANG - lemiyana lemiyana lemiyana (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) Universitas Islam Negeri (UIN), 2019)
This study aimed to test whether there is any influence between the investment and lifestyle the investor women customers of Bursa Efek Indonesia in Palembang city. The object of this study were investor women in capital market of Bursa Efek indonesia in Palembang city. The sampling methods collection used is the Non Probability sampling and Judgmental Sampling. The sampling taken as many as 150 investor women customers of Bursa Efek Indonesia in Palembang city. Further analysis of data using Structural Equation Model analysis techniques or SEM. The results of the testing that was done show that: first, the variable investment have significant influence on variable investor women customer’s Bursa Efek Indonesia in Kota Palembang. Second, the lifestyle variable has significant on variable investor women customer’s Bursa Efek Indonesia in Kota Palembang